Tourist image of Ustka in tourist's opinion - Krzysztof Parzych; Teresa Aniszewska (Kazimierz Wielki University, 2017)
The aim of this article was an analysis of the seaside polish resort  image in the tourist opinion. The town Ustka was used as a case study. Ustka is the one of the biggest seaside resorts in the middle part of the Pobrzeże Bałtyckie. The source of material for the purpose were results of the query made in the tourist season of the 2012 year in the beaches of Ustka and in the choosen tourist accommodation objects. Results show Ustka is very popular resort in the tourist opinion.